Pengaruh Debt Default, Kondisi Keuangan, dan Pertumbuhan Perusahaan terhadap Opini Audit Going Concern pada Perusahaan Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia - Rizky Agung Syah Putra; Widia Astuty; Eka Nurmala Sari (Jurnal Riset Akuntansi dan Bisnis, 2021)
This study aims to examine the effect of debt default, financial condition and company growth on going concern audit opinion on property and real estate companies listed on the Indonesia Stock Exchange (BEI) in 2014-2018. This research is a quantitative study using secondary data that can be accessed from the website / personal pages of property and real estate companies listed on the Indonesia Stock Exchange (IDX). This study uses criteria in determining the research sample. The research sample based on the criteria of 33 companies. The data analysis method used in this study is a statistical analysis method that uses logistic regression equations. Data analysis begins by processing data with Microsoft Excel, then testing is done using logistic regression. Logistic regression testing is used by using SPSS software. The results of this study indicate that: 1) Debt default has effect on going concern audit opinion; 2) Financial condition does not affect going concern audit opinion; 3) Company growth has effect on going concern audit opinion; 4) Debt default, financial condition, and company growth simultaneously influence going-concern audit opinion.